OPTIMALISASI KREATIVITAS PESERTA DIDIK MELALUI PENERAPAN PEMBELAJARAN DIFERENSIASI PRODUK - Nasrodin Nasrodin; Riza Faishol; Anis Fauzi (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2025)
21st century education requires the development of students' full potential, including creativity as one of the soft skills. However, existing learning is still teacher-centered and cognitively oriented, thus limiting students' creativity. Differentiated learning is a responsive approach to the diversity of readiness, interests, and learning styles of students. This research aims to optimize the creativity of students through the application of product differentiation learning at SMPN 1 Cluring. This study uses a qualitative descriptive approach with the subjects of PAI and Ethics teachers, students, curriculum representatives, Counseling Guidance teachers, and school principals. Data collection techniques include participatory observation, in-depth interviews, and documentation. Data analysis uses data condensation, data presentation, and conclusion drawn, data validity uses triangulation techniques and sources.The results of the study show that the application of product differentiation is able to foster the creativity of students, as seen from the variety of products produced, active participation in discussions, and increased initiative and courage to put forward ideas. Indicators of creativity that develop include critical thinking, emotional sensitivity, talent, and imagination in producing original works.